Intraindividual Evaluation of the Influence of Iterative Reconstruction and Filter Kernel on Subjective and Objective Image Quality in Computed Tomography of the Brain - Buhk, J. H.; Laqmani, A.; von Schultzendorff, H. C.; Hammerle, D.; Sehner, S.; Adam, G.; Fiehler, J.; Nagel, H. D.; Regier, M. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
Objectives: To intraindividually evaluate the potential of 4th generation iterative reconstruction (IR) on brain CT with regard to subjective and objective image quality.Methods: 31 consecutive raw data sets of clinical routine native sequential brain CT scans were reconstructed with IR level 0 (= filtered back projection), 1, 3 and 4; 3 different brain filter kernels (smooth/standard/sharp) were applied respectively. Five independent radiologists with different levels of experience performed subjective image rating. Detailed ROI analysis of image contrast and noise was performed. Statistical analysis was carried out by applying a random intercept model.Results: Subjective scores for the smooth and the standard kernels were best at low IR levels, but both, in particular the smooth kernel, scored inferior with an increasing IR level. The sharp kernel scored lowest at IR 0, while the scores substantially increased at high IR levels, reaching significantly best scores at IR 4. Objective measurements revealed an overall increase in contrast-to-noise ratio at higher IR levels, which was highest when applying the soft filter kernel. The absolute grey-white contrast decreased with an increasing IR level and was highest when applying the sharp filter kernel. All subjective effects were independent of the raters’ experience and the patients’ age and sex.Conclusion: Different combinations of IR level and filter kernel substantially influence subjective and objective image quality of brain CT.
Keywords: brain; CT; image manipulation/reconstruction